2007
DOI: 10.1126/science.1150799
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of a Human p110α/p85α Complex Elucidates the Effects of Oncogenic PI3Kα Mutations

Abstract: PIK3CA, one of the two most frequently mutated oncogenes in human tumors, codes for p110alpha, the catalytic subunit of a phosphatidylinositol 3-kinase, isoform alpha (PI3Kalpha, p110alpha/p85). Here, we report a 3.0 angstrom resolution structure of a complex between p110alpha and a polypeptide containing the p110alpha-binding domains of p85alpha, a protein required for its enzymatic activity. The structure shows that many of the mutations occur at residues lying at the interfaces between p110alpha and p85alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
510
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(534 citation statements)
references
References 57 publications
17
510
0
7
Order By: Relevance
“…In contrast, mutations in the helical domain (exon 9) cluster on an exposed surface patch of the protein and may change its ability to interact with other regulatory proteins, which may be different for each tissue. [31][32][33] As expected, analyses of the PTEN mutations revealed that these alterations are more common in pure endometrioid adenocarcinomas compared with that in non-endometrioid adenocarcinomas and mixed tumors. Different studies of colorectal and breast carcinomas have claimed that the PIK3CA and PTEN mutations are mutually exclusive and suggest that carcinogenic signaling through this pathway occurs either through the activation of PIK3CA or inactivation of PTEN.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, mutations in the helical domain (exon 9) cluster on an exposed surface patch of the protein and may change its ability to interact with other regulatory proteins, which may be different for each tissue. [31][32][33] As expected, analyses of the PTEN mutations revealed that these alterations are more common in pure endometrioid adenocarcinomas compared with that in non-endometrioid adenocarcinomas and mixed tumors. Different studies of colorectal and breast carcinomas have claimed that the PIK3CA and PTEN mutations are mutually exclusive and suggest that carcinogenic signaling through this pathway occurs either through the activation of PIK3CA or inactivation of PTEN.…”
Section: Discussionsupporting
confidence: 76%
“…3, A and B). The essential role of p110␣ in the heparanase-AKT pathway provides further molecular evidence for the tumorigenic properties of heparanase, because activating mutations in this isoform are oncogenic and have been found in many tumors (43,44). (iii) The activation of PI3K/AKT by heparanase was inefficient if the PI3K-RAS interaction was prevented (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, analysis of the relative positions of the nSH2 and iSH2 domains within p85ni by pulsed EPR spectroscopy in frozen solution suggest the presence of significant disorder between the nSH2 and iSH2 domains (K. I. Sen and G. J. Gerfen, unpublished observations). Furthermore, the identification of contacts between the C2 domain of p110␣ and residues around 560-564 in the iSH2 domain led to an alternative model, in which truncation at 572 would destabilize C2-iSH2 domain contacts that are required for inhibition of p110␣ (16,32).…”
mentioning
confidence: 99%
“…While NMR, EPR, and crystal structures have been obtained for the individual domains (7)(8)(9)(10)(11)(12)(13)(14)(15), there are currently no structures that define how these domains are arranged in space. The p110␣ catalytic subunit has been better defined, with structures of the N-terminal adapter-binding domain (ABD) or the entire p110␣ bound to the coiled coil (iSH2) domain of p85 (15,16). Like the related Class IB catalytic subunit p110␥ (17), p110␣ contains Ras-binding, C2, helical, and kinase domains.…”
mentioning
confidence: 99%